The Rhetoric of “Provision:” Public and Political Disputes over Port Planning in Hamburg in the 1970s and 1980s - Strupp, Christoph (International Planning History Society Proceedings, 2016)
Urban development projects are usually specific. There is a concrete designation of what the land is going to be used for – housing, commerce, leisure –, what buildings will be built and what infrastructure will be required. This enables a meaningful discussion of the proposed concepts and the balancing of public and particularistic interests. But what happens when areas are designated for development and cleared of inhabitants as a measure of economic “provision,” without a precisely defined purpose and with a time schedule stretching decades into the future? This paper will discuss this question in the form of a historical case-study on port expansion in Hamburg in the 1970s and 1980s. It will shed light on public and political conflicts, some of which were the result of particularities of port planning in general, some were the result of specifics of place and time. In 1961 the Hamburg state parliament designated 2,500 hectares for port expansion. It was to be used for new docks, but also for industry. In 1973 the evacuation of the village of Altenwerder began, to make sure that there would be time for the long process of preparing the land for new use. While port expansion had been welcomed unanimously in 1961, from the mid-1970s on it met with resistance. The law of 1961, which allowed for expropriation of private properties without a development scheme, did not hold up in court. Equally problematic was, that the policy of the Hamburg Senate of economic and industrial expansion and the underlying ideology of growth were now called into question. The alleged benefits for the city as a whole in terms of jobs and tax revenue were compared to the ecological and social costs of sacrificing Altenwerder. In 1982 a Port Expansion Law was passed to create a new legal basis for planning. The option of expropriating land for port purposes without a designation of its future use was included and the law allowed for industrial development in the port. To overcome public resistance, the Senate characterized port expansion preparation now in countless speeches and publications as an act of “provision.” Taking advantage of positive implications of the term from social politics – foresight, reason, rationality, responsibility –, the government maintained that it was not only necessary but actually its duty to take provisionary measures in the interest of economic prosperity. The rhetoric of “provision” did not bridge the ideological gap between politicians, port planners, environmentalists and private citizens directly affected by the expansion plans, but the public discourse calmed down after the completion of the evacuation of Altenwerder in the late 1980s, because no other areas of the plan of 1961 have been activated so far.